Ways of Seeing, Means for Knowing, Manners for Representing. Literature and Visual Culture in the Larra’s Journalistic Imaginary (Castilla. Estudios de Literatura, 2021)
This work examines how the optical devices popularised since the end of the 18th century, and the new visual regime to which they gave rise, affected the way we know and represent the world and how it affected the imaginary developed by Larra. To this purpose, it reviews the transformations related to vision technology, the way it affected the transmission of knowledge and the shaping of public opinion and, finally, how Larra, in his journalistic articles, tries to conciliate the power of the word with that of the new visual culture, which tries to capture the public's attention.
Keywords: Larra; Literary Imaginary; Visual Culture; Attention; Public Opinion